2001
DOI: 10.1002/1521-4141(200112)31:12<3504::aid-immu3504>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine interacts directly with its D3 and D2 receptors on normal human T cells, and activates β1 integrin function

Abstract: Dopamine by itself has not up to now been reported to activate T cell function. We show here that dopamine interacts directly with dopaminergic receptors on normal human T cells and triggers β1 integrin‐mediated T cell adhesion to a major extracellular matrix component, fibronectin (FN). Such adhesion is a characteristic feature of activated T cells, and is critical for trafficking and extravasation of T cells across blood vessels and tissue barriers. Seven dopamine D2/D3 receptor agonists and antagonists were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
92
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 126 publications
(97 citation statements)
references
References 47 publications
(67 reference statements)
2
92
0
3
Order By: Relevance
“…5). Similarly, Levite et al (25) reported that the activation of ␤ 1 integrin by dopamine was bell shaped with the optimal concentrations in the range of 10 to 100 nM. Thus, the biphasic type of dose responses may be in part responsible for such dichotomous activities.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…5). Similarly, Levite et al (25) reported that the activation of ␤ 1 integrin by dopamine was bell shaped with the optimal concentrations in the range of 10 to 100 nM. Thus, the biphasic type of dose responses may be in part responsible for such dichotomous activities.…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, they also demonstrated that a D3-selective agonist 7-OH-DPAT (1) mimicked and a D3-selective antagonist U-99194A (29) blocked the observed effects of dopamine (25). We have extended their observations and shown that dopamine as well as a D3-selective agonist 7-OH-DPAT (1) selectively induce adhesion of human naive CD8 ϩ T cells to fibronectin via D3 through activation of VLA-4 and VLA-5 integrins (Fig.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations